Vouchers to increase fruit affordability in Nigeria and Vietnam - Ambler, Kate; Brouwer, Inge D.; de Brauw, Alan; Herskowitz, Sylvan; Mai, Truong Tuyet; Pastori, Giulia; Samuel, Folake; Shittu, Oluyemisi; Talsma, Elise F. (Elsevier, 2026)
Although fruits are an important part of healthy diets, they are relatively expensive, so most individuals consume less than recommended. We use a randomized control trial to study a voucher program designed to improve the affordability of fruits in peri-urban and urban settings in Vietnam and Nigeria, and analyze whether vouchers can increase fruit consumption. The trial took place in 2021 among 601 households in Vietnam and 611 households in Nigeria. Vouchers were distributed between March and July in Vietnam and between June and November in Nigeria. In both contexts, a large majority of consumers who received vouchers used them. Following project conclusion, we find suggestive evidence of sustained increased fruit consumption only in Vietnam. In Nigeria, vouchers increased consumption of certain fruit categories during program implementation, but we find no evidence of sustained impacts. Fruit consumption is higher across the board in Vietnam, and the sample is wealthier overall, suggesting fruit affordability may not be a binding constraint for consumption. In Nigeria, the increase in consumption during the program along with a post-project decline suggest a lack of household resources to sustain consumption once the project concluded. The results suggest vouchers can improve consumption of healthy foods like fruits, but other actions are needed to make them more affordable in the longer term.